2018
DOI: 10.3389/fimmu.2017.01994
|View full text |Cite
|
Sign up to set email alerts
|

Equal Pro-inflammatory Profiles of CCLs, CXCLs, and Matrix Metalloproteinases in the Extracellular Microenvironment In Vivo in Human Dense Breast Tissue and Breast Cancer

Abstract: The inflammatory microenvironment affects breast cancer progression. Proteins that govern the inflammatory response are secreted into the extracellular space, but this compartment still needs to be characterized in human breast tissues in vivo. Dense breast tissue is a major risk factor for breast cancer by yet unknown mechanisms and no non-toxic prevention for these patients exists. Here, we used the minimal invasive technique of microdialysis for sampling of extracellular proteins in live tissues in situ in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 74 publications
(53 reference statements)
2
26
0
Order By: Relevance
“…This corroborates an in vivo study of inflammatory mediators in the microenvironment in healthy postmenopausal women were we found significant associations between reduced IL-1Ra/IL-1β ratio, increased levels of IL-6, IL-8, VEGF and CCL2 in breast tissue with extremely high MD compared to breast tissue with low MD (34). We have also shown that out of 32 pro-inflammatory mediators assessed, 26 proteins exhibited similar profiles in breast cancer and dense breast tissue suggesting a pro-inflammatory microenvironment as a possible initiator of malignant transformation in dense breast tissue (35).…”
Section: Resultssupporting
confidence: 54%
See 4 more Smart Citations
“…This corroborates an in vivo study of inflammatory mediators in the microenvironment in healthy postmenopausal women were we found significant associations between reduced IL-1Ra/IL-1β ratio, increased levels of IL-6, IL-8, VEGF and CCL2 in breast tissue with extremely high MD compared to breast tissue with low MD (34). We have also shown that out of 32 pro-inflammatory mediators assessed, 26 proteins exhibited similar profiles in breast cancer and dense breast tissue suggesting a pro-inflammatory microenvironment as a possible initiator of malignant transformation in dense breast tissue (35).…”
Section: Resultssupporting
confidence: 54%
“…MMP-9 has been associated with poor outcome in breast cancer patients but some experimental models have shown anti-tumoral effects on xenografts in mice (195,196,198,199). Furthermore, in a previous study by our group, no elevated levels of MMP-9 were measured in human breast cancers compared to adjacent normal breast tissue in vivo, whereas other MMPs were significantly elevated in breast cancer compared to adjacent normal breast tissue (35). This underlines the importance of studying the inflammatory mediators in their bioactive compartment.…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations